Resolution of Territorial Disputes in International Law - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
Territorial disputes in international law are resolved by peaceful means, like negotiations, mediation, conciliation, arbitration and in the procedure at the International Court of Justice. Borders between states are, in practice, determined on the basis of the uti possidetis iuris principle and principle of effective control. Historical arguments for territorial acquisition are not generally accepted, because changes of borders have to be a result of democratically expressed will of states. Also, the right of people for self-determination was used in the process of decolonization for creating new states but it has emerged in later years like in the case of East Timor, as a legal title for gaining independence. Apart from the process of decolonization, the right to self-determination is rather unclear and disputable regarding its scope and content. Traditional modes of territorial acquisition still have decisive role in international law. Almost all states rely on them in order to substantiate their claims for possession of certain territories. Therefore, international courts and arbitrations cannot ignore them.